SHARED DECISION-MAKING MODEL: DECISION MAKING OF LONG-TERM CONTRACEPTION METHOD - Sari Wahyuni; Desy Setiawati; Elga Mardani; Siti Hindun; Nia Clarasari Mahalia Putri (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2022)
Backgroud: Family planning is an effort to increase awareness and participation in realizing a happy and prosperous small family. The efforts by the National Population and Family Planning Agency to reduce Maternal Mortality Ratio in Indonesia are by increasing family planning participation and use the Long-Term Contraception Method through fertility regulation in family planning policies implemented to assist married couple on decision making, the shared decision-making is one of model that can be used by health care providers for helping patients make a health decision. Purpose: Known the influence of shared decision-making model on decision making of long- term contraception method at the BPM and RB in Palembang City in 2020. Methods: The study uses a pre experimental design with a static group comparison design. The samples were took by accidental sampling technique, which 80 respondents were divided into 40 respondent in the control group and 40 other respondents in the experiment group. Results: Based on univariat results in the control group it was found that the majority of mothers (72,5%) chose to continue using current contraception and in experiment group there were 12 mothers (30%) who chose and had used long-term contraception. The results of statistic analysis using the Chi-Square test with a significance level of 5% obtained the results of Pearson Chi-Square p = 0,002 which means the shared decision-making model has influence on decision making of long-term contraception method at the BPM and RB in Palembang City. Conclusion: There is a significant the influence of shared decision-making model on decision making of long-term contraception method at the BPM and RB in Palembang City in 2020